APPLICATION OF AHP FOR SUPPLIER SELECTION IN CONSTRUCTION COMPANIES - Eddy Nugroho, Rosalendro; Maria Sherly Iskandar (Dinasti Publisher, 2020)
The procurement process is an important process in supply chain management as it is the spearhead of the entire process. In carrying out the procurement process, there are often problems with the supplier selection activities. This is because the supplier selection process spends a lot of time and resources collecting data and conducting careful analysis that will affect the entire decision alternative. In making decisions relating to the many criteria and the number of alternative suppliers, it requires an effective and uncomplex assessment technique, but it provides accurate results. A mapping and determination of supplier selection criteria is required as a basis for valuation to obtain a qualified supplier. This study focused on PT. XYZ is a construction company in South Tangerang. Analytical Hierarchy Process (AHP) is used to determine the best supplier, there are 4 variables that are reference in conducting the selection of suppliers, such as: cost, quality, delivery, and service. The result in the selection of the supplier company is cost with a weight of 0.268, quality with a weight of 0.290, delivery with a weighting of 0.248, and the service with a weight of 0.194 where conclusions obtained from the analysis of the selection of the best suppliers and in accordance with the criteria, namely PT. CBL for iron suppliers, PT.SAS for cement suppliers, and PT. Citra BSD for suppliers of natural materials